A fibrinogen-related Lectin from Echinometra lucunter represents a new FReP family in Echinodermata phylum. Issue 131 (December 2022) - Duarte, Philippe Lima; Andrade, Francisco Regivânio Nascimento; Sousa, Andressa Rocha de Oliveira; Andrade, Alexandre Lopes; de Vasconcelos, Mayron Alves; Teixeira, Edson Holanda; Nagano, Celso Shiniti; Sampaio, Alexandre Holanda; Carneiro, Rômulo Farias
Abstract: Fibrinogen-related proteins (FREPs) have been identified in several animals. They are involved in the body's defense, acting as mediators of phagocytosis. Ficolins and intelectins are some of the most studied Fibrinogen-related Domain (FReD)-containing lectins. In this work, we have isolated a singular FReD-containing lectin, which cannot be classified as ficolin or intelectin. ELL ( Echinometra lucunter lectin) was isolated from coelomic plasma by affinity chromatography on xanthan gum. Primary structure was determined by tandem mass spectrometry. Moreover, antimicrobial activity of ELL was evaluated against planktonic cells and biofilm of Escherichia coli, Staphylococcus aureus and S. epidermidis . ELL showed hemagglutinating activity in Ca 2+ presence, which was inhibited by glycoprotein mucin and thyroglobulin. Complete amino acid sequence consisted of 229 residues, including a FReD in the N-terminal. Searches for similarity found that ELL was very close to putative proteins from Strongylocentrotus purpuratus . ELL showed moderate similarity with uncharacterized sea stars proteins and protochordate intelectins. ELL was able to inhibit the planktonic growth of the Gram-positive bacteria and significantly reduce the biofilm formation of all bacteria tested. In conclusion, we identified a new type of FReP-containing lectin with some structural and functional conservation towards intelectins. Highlights: A Fibrinogen-related protein (FREP) was isolated from sea urchin Echinometra lcuunter . ELL she is the first member of a new family of FREPs found in echinoderms. ELL seems to be involved in the defense of the E. lucunter . ELL was able to inhibit the planktonic growth of the Gram-positive bacteria.